Neuroeducational research in the design and use of a learning technology - Howard-Jones, Paul; Holmes, Wayne; Demetriou, Skevi; Jones, Carol; Tanimoto, Eriko; Morgan, Owen; Perkins, David; Davies, Neil (My University, 2015)
Many have warned against a direct 'brain scan to lesson plan' approach when attempting to transfer insights from neuroscience to the classroom. Similarly, in the effective design and implementation of learning technology, a judicious interrelation of insights associated with diverse theoretical perspectives (e.g., neuroscientific, pedagogical and classroom praxis) may be required. A design-based research approach to the development of learning technology informed by neuroscience may be one way of achieving this interrelation. Accordingly, here we report on some of the preliminary research of a web app, known as 'zondle Team Play', that allows teachers to teach whole classes using a games-based approach and which draws on concepts from neuroscience. Rather than just exploring 'what works' in terms of the technology, low-fidelity prototyping and participant design helped us explore aspects of praxis and affordances of the technological design that were contingent upon each other. Five cycles of design, intervention, analysis and reflection revealed some potential benefits of a neuroeducational approach to learning technology design, including the development of related pedagogy, identification of immediate and future neuroeducational research questions and the development of language and terms suitable for communicating across interdisciplinary boundaries.
Keywords: Technology; Games; Rewards; Neuroscience; Pedagogy; Teaching